2001
DOI: 10.1128/jcm.39.12.4526-4528.2001
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Relationship between U.S. and French Serotype V Group B Streptococcus Isolates

Abstract: We examined the genetic diversity of serotype V group B streptococcus (GBS) isolates in the Paris area and compared them with the predominant American serotype V clone. Pulsed-field gel electrophoresis yielded 11 patterns for 64 French GBS. One pattern was obtained with 60% of the isolates tested and was indistinguishable from that of the predominant American clone.Group B streptococci (GBS) are the main cause of severe infection in both infants and adults (2,20,21). GBS are serotyped on the basis of their cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
10
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
5
10
1
Order By: Relevance
“…Extension of PFGE analysis to 21 erythromycinsensitive serotype V isolates revealed diversity within the GBS serotype V population as well as one predominant RDP (pattern B) accounting for 48% of all sensitive serotype V isolates (10 of 21). These findings are in good agreement with data published in previous studies (8,14). Even though direct comparative analysis of our isolates with the predominant U.S. or French serotype V GBS strains was not performed in this work, the B pattern obtained from the majority of our isolates seems to be very similar to the pattern published as being predominant in the United States and France.…”
supporting
confidence: 82%
“…Extension of PFGE analysis to 21 erythromycinsensitive serotype V isolates revealed diversity within the GBS serotype V population as well as one predominant RDP (pattern B) accounting for 48% of all sensitive serotype V isolates (10 of 21). These findings are in good agreement with data published in previous studies (8,14). Even though direct comparative analysis of our isolates with the predominant U.S. or French serotype V GBS strains was not performed in this work, the B pattern obtained from the majority of our isolates seems to be very similar to the pattern published as being predominant in the United States and France.…”
supporting
confidence: 82%
“…Genetic diversity among type V isolates has also been observed by Thomas-Bories et al (17), as they found 11 distinct patterns in 64 isolates. In contrast to our V/R1,R4 isolates, the NT/R1,R4 isolates appeared to have retained genetic homogeneity, with three-quarters still classified within PFGE profile 4.…”
Section: Discussionsupporting
confidence: 53%
“…Similarly, Fasola et al (1993) and Ferrieri et al (1997) obtained more SmaI PFGE patterns than REA with HindIII or HindIII followed by EcoRI and conventional agarose gel electrophoresis. Many researchers who used PFGE analysis of GBS strains have documented considerable genetic diversity among strains of similar serotypes (Fasola et al, 1993;Rolland et al, 1999;Le Thomas-Bories et al, 2001;Moyo et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, PFGE is the most versatile and powerful technique for the study of chromosomal relatedness among bacterial strains as it is reproducible and very discriminative. Many researchers have demonstrated the discriminatory ability and reliability of PFGE in further differentiation of GBS strains of the same serotype (Rolland et al, 1999;Le Thomas-Bories et al, 2001;Benson et al, 2002;Moyo et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation